Respuesta :

frika

Answer:

x = 3

y = 3

Step-by-step explanation:

To solve x - 3y = -6 and 2x - y = 3 using equal value method, express othe same variable from each equation.

1st equation:

[tex]x=3y-6[/tex]

2nd equation:

[tex]2x=y+3\\ \\x=\dfrac{1}{2}(y+3)[/tex]

Equate the right sides of these expressions:

[tex]3y-6=\dfrac{1}{2}(y+3)[/tex]

Multiply by 2:

[tex]6y-12=y+3\\ \\6y-y=3+12\\ \\5y=15\\ \\y=\dfrac{15}{5}\\ \\y=3[/tex]

Substitute it into the first expression:

[tex]x=3\cdot 3-6\\ \\x=9-6\\ \\x=3[/tex]